The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/anie.202106047
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Metal Anodes Working at 60 mA cm−2 and 60 mAh cm−2 through Nanoscale Lithium‐Ion Adsorbing

Abstract: Achieving high-current-density and high-areacapacity operation of Li metal anodes offers promising opportunities for high-performing next-generation batteries. However, high-rate Li deposition suffers from undesired Liion depletion especially at the electrolyte-anode interface, which compromises achievable capacity and lifetime. Here, electronegative graphene quantum dots are synthesized and assembled into an ultra-thin overlayer capable of efficient Liion adsorbing at the nanoscale on Li-metal to fully reliev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…CE performance was first examined in the half-cell configuration assembled by pairing the routine Li metal with D-Cu@CuSe, while B-Cu-and D-Cu-based half cells were also constructed for comparison. [37][38][39] It is interesting to note that an apparent discharge platform can be observed at %0.8 V (vs. Li/Li þ ) during the initial electrochemical activation process (Figure S9, Supporting Information). Correspondingly, the characteristic peaks assigned to Li 2 Se in the XRD pattern further verify the in situ generation of the Li 2 Se protective layer (Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…CE performance was first examined in the half-cell configuration assembled by pairing the routine Li metal with D-Cu@CuSe, while B-Cu-and D-Cu-based half cells were also constructed for comparison. [37][38][39] It is interesting to note that an apparent discharge platform can be observed at %0.8 V (vs. Li/Li þ ) during the initial electrochemical activation process (Figure S9, Supporting Information). Correspondingly, the characteristic peaks assigned to Li 2 Se in the XRD pattern further verify the in situ generation of the Li 2 Se protective layer (Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, we synthesized zero-dimensional quantum-sized graphene dots and then constructed an ultrathin Li + adsorbing layer (LAL) on Li metal surface (Figure 6c, d). [68] The graphene quantum dots exhibited typical sizes of 3-5 nm, and they were comprised of nanocrystalline carbon cores with surface polar functional groups (e. g., À OH, À NH 2 , C=O/C=N, and C=S). This unique quantum-sized graphene dots could localize the sp 2electrons that induced attraction forces toward Li + .…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
“…e) Schematic of the preparation process and design rationale of the graphene quantum dot building blocks for the LAL. Reproduced with permission [68] . Copyright 2021, Wiley‐VCH.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [ 33 ] reported that 2D MnZnO nanosheets/CNF infused with molten Li maintained 40 h at 50 mA cm −2 and 10 mAh cm −2 . Nevertheless, the modified Li anodes with high areal capacities (> 10 mAh cm −2 ) can only be performed (< 1000 h) at limited current densities (< 10 mA cm −2 ) [ 53 55 ]. Therefore, a rational design of lithiophilic material remains unclear for protecting Li metal anode toward practical application (especially at ultrahigh current density and areal capacity).…”
Section: Introductionmentioning
confidence: 99%